137Cesium i myrsamhällen i Gävleborgs län 24 år efter Tjernobylolyckan - Brandström , Linnea (SLU/Dept. of Soil and Environment, 2010)
24 years have passed since the Chernobyl accident when radionuclides were spread over large areas of Europe, including the Scandinavian countries. Today, measurable activities of 137Cs are still observed in many Swedish ecosystems.